2020
DOI: 10.1155/2020/4935831
|View full text |Cite
|
Sign up to set email alerts
|

The CC Genotype of Insulin-Induced Gene 2 rs7566605 Is a Protective Factor of Hypercholesteremia Susceptible to Mild Cognitive Impairment, Especially to the Executive Function of Patients with Type 2 Diabetes Mellitus

Abstract: Backgrounds and Aims. Insulin-induced gene 2 (INSIG-2) is closely related to hypercholesteremia, which is a well-recognized risk factor of mild cognitive impairment (MCI) in type 2 diabetes mellitus (T2DM). We aim to investigate the association between promoter of the INSIG-2 rs7566605 single-nucleotide polymorphism (SNP) and T2DM with MCI. Methods. 233 T2DM patients with MCI or without MCI were recruited. Baseline data and genotype frequency were compared between MCI and non-MCI groups. Demographic parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…LDL-C level was positively associated with execution function in patients with hypercholesteremia. Similarly, our latest results show that hypercholesteremia, especially increased LDL-C may influence the executive function of patients with T2DM [ 49 ]. Additionally, Xia et al demonstrated the disordered functional connectivity of bilateral hippocampus-middle frontal gyrus in diabetic patients with poorly controlled LDL-C, and associated with executive function [ 13 ].…”
Section: Discussionmentioning
confidence: 86%
“…LDL-C level was positively associated with execution function in patients with hypercholesteremia. Similarly, our latest results show that hypercholesteremia, especially increased LDL-C may influence the executive function of patients with T2DM [ 49 ]. Additionally, Xia et al demonstrated the disordered functional connectivity of bilateral hippocampus-middle frontal gyrus in diabetic patients with poorly controlled LDL-C, and associated with executive function [ 13 ].…”
Section: Discussionmentioning
confidence: 86%
“…However, functional distinctions may exist between INSIG1 and INSIG2 in that they are differentially regulated by metabolic hormone and metabolites [ 52 , 53 ]. Several studies have found that INSIG2 genetic polymorphisms are associated with the metabolic syndrome [ [53] , [54] , [55] ], while the common variation in INSIG1 is unlikely to have a major effect on type 2 diabetes and obesity risk [ 56 ]. Further understanding of the regulatory and functional differences between INSIG1 and INSIG2 may provide a new way to explain the preferential interaction between CD36 and INSIG2.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, we found higher HbA1c level, in T2DM patients with MCI than these without MCI. 51 , 52 These factors may limit the accuracy of results as confounding factors for a cross-section study. So, in the later analysis, these factors were corrected.…”
Section: Discussionmentioning
confidence: 99%